(untitled) (Revista Argentina de Cirugía, 2026)
Gastrointestinal stromal tumors (GISTs) are becoming an increasingly common reason for consultation in gastroenterology surgery interviews. Patients are usually referred for surgery due to an incidental finding or symptoms associated with tumor growth. We report the case of a female patient who required urgent hospitalization due to acute anemic syndrome. The diagnostic algorithm and surgical approach are described. The current standards of diagnosis and treatment are also discussed, with special focus on the surgical strategy, which must be tailored to each case.